Polythene and Plastics-degrading microbes from the mangrove soil - Kathiresan, K (Revista de Biología Tropical, 2003)
Biodegradation of polythene bags and plastic cups was analyzed after 2, 4, 6, and 9 months of incubation in the mangrove soil. The biodegradation of polythene bags was significantly higher (up to 4.21% in 9 months) than that of plastic cups (up to 0.25% in 9 months). Microbial counts in the degrading materials were recorded up to 79.67 x 104 per gram for total heterotrophic bacteria, and up to 55.33 x 102 per gram for fungi. The microbial species found associated with the degrading materials were identified as five Gram positive and two Gram negative bacteria, and eight fungal species of Aspergillus. The species that were predominant were Streptococcus, Staphylococcus, Micrococcus (Gram +ve), Moraxella, and Pseudomonas (Gram –ve) and two species of fungi (Aspergillus glaucus and A. niger). Efficacy of the microbial species in degradation of plastics and polythene was analyzed in shaker cultures. Among the bacteria, Pseudomonas species degraded 20.54% of polythene and 8.16% of plastics in one-month period. Among the fungal species, Aspergillus glaucus degraded 28.80% of polythene and 7.26% of plastics in one-month period. This work reveals that the mangrove soil is a good source of microbes capable of degrading polythene and plastics.